The Hustle - Addison, Chris 1971; Shapiro, Stanley; Henning, Paul, 1911-2005; Launer, Dale; Schaeffer, Jac; Birnbaum, Roger; Hathaway, Anne, 1982-; Wilson, Rebel; Sharp, Alex, 1989-; Norris, Dean; Simons, Timothy; Oliver, Ingrid, 1977-; et al. (Universal City, CA : Universal Pictures Home Entertainment, 2019)
Josephine Chesterfield is a glamorous, seductive Brit who defrauds gullible wealthy men. Penny amasses wads of cash by ripping off her marks in neighborhood bars. Despite their different methods, both are masters of the art of the fleece, so they combine talents for their next mark: a naive tech billionaire.
Originally released as a motion picture in 2019.
Adapted from the film "Dirty Roten Scoundrels" (1988).
Wide screen.
Special features: Hitting the mark; Comedy class; Con artists; Feature commentary by director Chris Addison.
Keywords: Swindlers and swindling -- Drama; Man-woman relationships -- Drama; Comedy films; Crime films; Feature films; Fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities